2015
DOI: 10.1016/j.artmed.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Interpretative reading of the antibiogram – a semi-naïve Bayesian approach

Abstract: A practical method for predicting probability for antimicrobial susceptibility could be developed based on a semi-naïve Bayesian approach using statistical data on cross-susceptibilities and cross-resistances. The reduction in Brier distance from 37.7% to 25.3%, indicates a significant advantage to the proposed min2max2 method (p<10(99)).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
1
3
0
1
Order By: Relevance
“…Such MIC variation could be due to the particular characteristics of each clinical isolate, such as membrane composition, protease secretion, etc. [59] and has been also described for antimicrobial testings [60]. The acquired antimicrobial drug resistance attributed to the biofilm formation was also observed for the isolates studied here.…”
Section: Discussionsupporting
confidence: 63%
“…Such MIC variation could be due to the particular characteristics of each clinical isolate, such as membrane composition, protease secretion, etc. [59] and has been also described for antimicrobial testings [60]. The acquired antimicrobial drug resistance attributed to the biofilm formation was also observed for the isolates studied here.…”
Section: Discussionsupporting
confidence: 63%
“…Moreover, a recent randomized controlled trial on a WISCA antibiotic stewardship clinical decision support tool conducted in the US, found that providers in the intervention group followed recommendations to change antibiotics 60% of the time. [10] As previously noted in other studies, [11][12][13] there are still analytical challenges in the WISCA development, represented mainly by the paucity of data in the different strata in the models that can be overcome using Bayesian methods.…”
Section: Introductionmentioning
confidence: 92%
“…‘Interpretative reading’ is a core methodology employed by clinicians and involves analysing the susceptibility pattern of a given organism, not just the results of individual antibiotics. 13 , 14 , 31 Commercially available automated test systems employ different variations of what are known as ‘expert test systems’. These systems are computers that use data to simulate human decision-making and use facts to infer what is already known.…”
Section: Step 1 Collaborate With the Clinical Microbiology Laboratory...mentioning
confidence: 99%